Novel MYC-driven medulloblastoma models from multiple embryonic cerebellar cells - Kawauchi, Daisuke; Korshunov, Andrey; Lichter, Peter; Kool, Marcel; Pfister, Stefan (Oncogene, 2017)
Group3 medulloblastoma (MBG3) that predominantly occur in young children are usually associated with MYC amplification and/or overexpression, frequent metastasis and a dismal prognosis. Physiologically relevant MBG3 models are currently lacking, making inferences related to their cellular origin thus far limited. Using in utero electroporation, we here report that MBG3 mouse models can be developed in situ from different multipotent embryonic cerebellar progenitor cells via conditional expression of Myc and loss of Trp53 function in several Cre driver mouse lines. The Blbp-Cre driver that targets embryonic neural progenitors induced tumors exhibiting a large-cell/anaplastic histopathology adjacent to the fourth ventricle, recapitulating human MBG3. Enforced co-expression of luciferase together with Myc and a dominant-negative form of Trp53 revealed that GABAergic neuronal progenitors as well as cerebellar granule cells give rise to MBG3 with their distinct growth kinetics. Cross-species gene expression analysis revealed that these novel MBG3 models shared molecular characteristics with human MBG3, irrespective of their cellular origin. We here developed MBG3 mouse models in their physiological environment and we show that oncogenic insults drive this MB subgroup in different cerebellar lineages rather than in a specific cell of origin.